Post-Truth Imaginations New Starting Points for Critique of Politics and Technoscience - Rommetveit, Kjetil (History and Philosophy of Technoscience, 2022)
This book engages with post-truth as a problem of societal order and for scholarly analysis. It claims that post-truth discourse is more deeply entangled with main Western imaginations of knowledge societies than commonly recognised. Scholarly responses to post-truth have not fully addressed these entanglements, treating them either as something to be morally condemned or as accusations against which scholars have to defend themselves (for having somehow contributed to it). Aiming for wider problematisations, the authors of this book use post-truth to open scholarly and societal assumptions to critical scrutiny. Contributions are both conceptual and empirical, dealing with topics such as: the role of truth in public; deep penetrations of ICTs into main societal institutions; the politics of time in neoliberalism; shifting boundaries between fact - value, politics - science, nature - culture; and the importance of critique for public truth-telling. Case studies range from the politics of nuclear power and election meddling in the UK, over smart technologies and techno-regulation in Europe, to renewables in Australia. The book ends where the Corona story begins: as intensifications of Modernity's complex dynamics, requiring new starting points for critique.